International perspective on social cognition in schizophrenia: current stage and the next steps - Silvia Corbera; Matthew M. Kurtz; Amélie M. Achim; Giulia Agostoni; Isabelle Amado; Michal Assaf; Stefano Barlati; Margherita Bechi; Roberto Cavallaro; Satoru Ikezawa; Hiroki Okano; Ryo Okubo; et al. (European Psychiatry)
In the last decades, research from cognitive science, clinical psychology, psychiatry, and social neuroscience has provided mounting evidence that several social cognitive abilities are impaired in people with schizophrenia and contribute to functional difficulties and poor clinical outcomes. Social dysfunction is a hallmark of the illness, and yet, social cognition is seldom assessed in clinical practice or targeted for treatment. In this article, 17 international experts, from three different continents and six countries with expertise in social cognition and social neuroscience in schizophrenia, convened several meetings to provide clinicians with a summary of the most recent international research on social cognition evaluation and treatment in schizophrenia, and to lay out primary recommendations and procedures that can be integrated into their practice. Given that many extant measures used to assess social cognition have been developed in North America or Western Europe, this article is also a call for researchers and clinicians to validate instruments internationally and we provide preliminary guidance for the adaptation and use of social cognitive measures in clinical and research evaluations internationally. This effort will assist promoting scientific rigor, enhanced clinical practice, and will help propel international scientific research and collaboration and patient care.